THE NEW INTERNATIONAL DICTIONARY OF QUOTATIONS - Miner, Margaret, editor 333162; Rawson, Hugh, editor 640999 (New York, N.Y. : A Signet Book, 1994)
Cross-referenced by subject and indexed by author, this volume serves as an indispensable guide to over 3700 quotes by famous authors and speakers.